Comparison between pork and wild boar meat (sus scrofa) by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP)(Perbandingan di antara daging babi dan babi hutan (Sus scrofa) dengan menggunakan analisis tindak balas rantaian Polymerase-Polimorfisme panjang cebisan pemotongan (PCR-RFLP) - Sahilah Abd. Mutalib; Wan Sakeenah Wan Nazri; Safiyyah Shahimi; Norhayati Yaakob; Norrakiah Abdullah Sani; Aminah Abdullah; Abdul Salam Babji; Maaruf Abd. Ghani (Universiti Kebangsaan Malaysia, 2012)
A method of PCR-restriction fragment length polymorphism (RFLP) has been utilized to differentiate the mitochondrial genes of pork and wild boar meat (Sus scrofa). The amplification PCR products of 359 bp and 531 bp were successfully amplified from the cyt b gene of these two meats. The amplification product of pork and wild boar using mt-12S rRNA gene successfully produced a single band with molecular size of 456 bp. Three restriction endonucleases (AluI, HindIII and BsaJI) were used to restrict the amplification products of the mitochondrial genes. The restriction enzymes of AluI and BsaJI were identified as potential restriction endonucleases to differentiate those meats. HindIII enzyme was unable to restrict the PCR product of both meats. The genetic differences within the cyt b gene among the two meats were successfully confirmed by PCR-RFLP analysis